DETERMINAN LITERASI KEUANGAN PADA GENERASI MILENIA DI KOTA SEMARANG - Fuadi, Faiq; Kusumawati, Dyah (Universitas YPPI Rembang, 2023)
This research was conducted with the intention of determining the influence of financiaI knowledge, financiaI attitudes and financiaI behavior on financial literacy in the millennial generation in Semarang City. Sampling was taken using an accidental sampling and purposive sampling approach of 101 respondents. Research data analysis uses vaIidity test, reIiability test, correIation coefficient test, coefficient of determination test, simpIe linear regression analysis, multipIe linear regression anaIysis, t test, and F test using the IBM SPSS Statistics version 25 tool. The SPSS test results show that partial financial knowledge and financial behavior variables have a positive effect on financial literacy, while financial attitudes have no effect on financial literacy. Simultaneously all variabIes of financial knowledge, financiaI attitudes, financial behavior have a positive effect on financiaI literacy. There needs to be outreach about the importance of financiaI literacy in schools/ higher education. Apart from that, other research still needs to be carried out with different independent variables. Keywords: financial knowIedge, financial attitudes, financiaI behavior, financial literacy